(untitled) (The Batuk, 2022)
People of Nepal and India share similar civilization having open border through which citizens of both countries easily migrate in each-others’ countries with no obstacles for lawful work. Mostly, people of both countries migrate for job but Nepalese people migrate to join in British – Indian regiments too and some people migrate for long term settlement and some are for illegal flesh trade. This article has dealt about Nepalese and Indian migrants in both countries and its scenario in an analytical ways on the basis of qualitative research method being centralized to the objectives of this research work. This study also focuses on economic, social, cultural and political prospects and impact of migration in both the countries.